Is ultraviolet exposure acquired at work the most important risk factor for cutaneous squamous cell carcinoma? Results of the population‐based case–control study FB‐181 - Schmitt, J.; Haufe, E.; Trautmann, F.; Schulze, H.‐J.; Elsner, P.; Drexler, H.; Bauer, A.; Letzel, S.; John, S.M.; Fartasch, M.; Brüning, T.; Seidler, A.; et al. (British journal of dermatology (1951), 2018)
Summary Squamous cell carcinoma (SCC) is a specific type of skin cancer. It is one of the most common cancers in Europe. SCC therefore causes a significant burden, both for the people affected and also in terms of costs to society. One main cause of SCC is exposure to natural sunlight. SCC can be prevented by avoiding sun exposure. When people go outside, they can protect themselves through clothes (e.g. long sleeves, hat) and using sunscreens. Until now, prevention programs for SCC and other skin cancers have mainly tried to reduce sun exposure during leisure time. However, there are many people working outdoors, e.g. farmers, construction workers and roofers. The role of occupational (work‐related) and leisure‐time sun exposure in causing SCC is still unclear. Our team of physicians and scientists from Germany investigated the association between occupational and leisure‐time sun exposure and the risk of SCC. More than 600 people with SCC were compared to the same number of healthy people without SCC, taking into account their sun exposure in the past. All study participants were medically examined by trained physicians. Lifetime sun exposure in occupation and leisure time was assessed by interviews. The interviews were tested before starting the study to ensure correct results. The study found that people with high levels of sun exposure at work have a 2‐fold risk of SCC. The more sun exposure people had at work, the more likely was the development of SCC. This result is important, as it indicates that sun protection is not only necessary in leisure‐time, but also at work to prevent skin cancer such as SCC. Linked Article: Schmitt et al. Br J Dermatol 2018; 178:462–472